تأثير الكثافة النباتية ومواعيد الزراعة في إنتاجية بعض أصناف فول الصويا تحت ظروف منطقة الساحل السوري - رقية, نزيه; محمد, يوسف; قاجو, أولا (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال الموسمين الزراعيين 2006، 2007 في مزرعة بوقا التابعة لكّلية الزراعة- جامعة تشرين على ثلاثة أصناف من فول الصويا هي Sb-273 , Sb-314 , Sb-44. تمت الزراعة في موعدين: رئيس 10 أيار وتكثيفي 15 حزيران بكثافتين نباتيتين 200، 400 ألف نبات/هـ. أشارت النتائج إلى مايأتي: - تفّوق الصنف Sb-273 على بقية الأصناف (Sb-314، Sb-44) في معاملات التجربة كافّة ، ولمعظم المؤشرات المدروسة، وسجل أعلى إنتاجية من البذور (5298.89 كغ/هـ) مقارنة مع الصنفين الآخرين. - تفوقت الزراعة بكثافة 400 ألف نبات/هـ للأصناف المدروسة مقارنةً بزراعتها بكثافة 200 ألف نبات/هـ. - تفّوق الموعد الرئيس لزراعة فول الصويا (10 أيار) على الموعد التكثيفي (15حزيران) عند الأصناف المدروسة ولجميع الصفات ما عدا صفة وزن الـ 100 بذرة. This search is conducted on Bouka Farm affiliated with the Faculty of Agriculture at Tishreen University during 2006 and 2007 growing seasons, using three Soybean cultivars Sb-44, Sb-314 and Sb-273. seeds have been sown on the tenth of May and fifteenth of June, being the main and intensive planting dates, respectively; botanic densities are 200 and 400 thousand plants/h., and the results demonstrate the following: 1) For most parameters at issue, cultivar Sb-273 is the best of all others (Sb-44, Sb-314) in all treatments, and has recorded the highest seed yield (5298.89kg/h) in comparison with the other two cultivars. 2) A botanic density of 400 thousand plants/h has proven to be better than other tested botanic density of the cultivars concerned. 3) A main planting date (10th May) has proven to be better than the intensive planting date (15th June) of both the cultivars and parameters concerned except for the weight of (100) seeds.